Streptococcus pyogenes: disease and molecular pathogenesis 2 - Cleary, P. Patrick (Henry Stewart Talks, 2026)
S. pyogenes, Resistance to phagocytosis, C5a peptidase, Human C5a, M protein, Superantigens, Adhesins and invasins